Evaluation of tooth loss as a permanent mark on the face - Balcı, Yasemin; Gürpınar, Kağan; Afşin, Hüseyin; Çolak, Başar (The Bulletin of Legal Medicine, 2021)
Aim: The aim of this study is to contribute to the implementation partnership by determining the opinions about “whether the traumatic tooth loss is accepted as a permanent mark on the face or not” within the framework of the Turkish Penal Code.Method: In the study, an informative text was presented to forensic medicine specialist, dentists and judiciary, containing different views. Then, a questionnaire including their areas of expertise, their province, duration of experience, and their opinions on the subject was applied. The survey data were analyzed and evaluated through a statistical program.Results: A total of 162 people, 103 of whom were forensic medicine specialists, 38 lawyers and 21 dentists, participated in the survey. The 38.8% of forensic medicine specialists, 90.5% of dentists and 34% of lawyers are working in Istanbul, Ankara, Izmir. 61.1% of the participants have 10 (-) years of experience, 38.5% have 11(+) years of experience. The forensic medicine specialists are significantly higher in the group of 10 (-) year experienced group (p 0.05). The opinions expressed by the participants in writing were also presented.  Conclusion: The general approach is to evaluate the incurable tooth loss as permanent mark on the face.
Keywords: Permanent mark; Tooth loss; Forencis medicine; Turkish Penal Code